2021
DOI: 10.1136/bmjopen-2020-040775
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory and olfactory dysfunctions in hospitalised patients with COVID-19 pneumonia: a prospective study

Abstract: ImportanceIdentifying undetected clinical signs is imperative in the prevention of SARS-CoV-2.ObjectiveTo establish the prevalence of clinical gustatory and olfactory dysfunctions in patients with COVID-19 pneumonia. Clinical outcomes and recovery rates associated with gustatory and olfactory dysfunctions were also assessed.DesignA prospective study was performed in 80 patients admitted to Hospital Clínic of Barcelona (Spain) for COVID-19 pneumonia. Patients were re-evaluated in the ward daily until discharge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…The authors speculate that short lived olfactory dysfunction may simply be overlooked in more severe disease due to over-riding respiratory symptoms and associated anorexia leading to reduced dietary intake and they suggest that any association between OD and a milder course is an artefact. Similar findings were reported by an independent research group in Spain [13]…”
Section: Prevalence and Presentation Of Olfactory Loss In Covid-19supporting
confidence: 92%
See 1 more Smart Citation
“…The authors speculate that short lived olfactory dysfunction may simply be overlooked in more severe disease due to over-riding respiratory symptoms and associated anorexia leading to reduced dietary intake and they suggest that any association between OD and a milder course is an artefact. Similar findings were reported by an independent research group in Spain [13]…”
Section: Prevalence and Presentation Of Olfactory Loss In Covid-19supporting
confidence: 92%
“…The authors speculate that short lived olfactory dysfunction may simply be overlooked in more severe disease due to over-riding respiratory symptoms and associated anorexia leading to reduced dietary intake and they suggest that any association between OD and a milder course is an artefact. Similar findings were reported by an independent research group in Spain [13] One study has suggested that anosmia may be more frequent among women (72.4%; 95% CI, 62.8%-80.7%) than among men (55.7%; 95% CI, 45.2%-65.8%; P ¼ 0.02) [14]. A systematic review suggested a lower reporting of OD with increasing age [15], in keeping with age dependent reduced expression of Angiotensin-converting enzyme 2.…”
Section: Prevalence and Presentation Of Olfactory Loss In Covid-19supporting
confidence: 92%
“…Previous research has shown that olfactory and gustatory impairment can occur alone or in combination with other COVID-19 symptoms [ 48 , 49 ]. Inciarte et al demonstrated a significant association between olfactory and gustatory dysfunction and the development of additional symptoms such as cough and hyporexia [ 50 ]. While numerous studies have found no link between olfactory/gustatory dysfunction and rhinorrhea or nasal blockage development, others have reported a possible association [ 24 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Necropsies have confirmed brain edema and neuronal degeneration in patients who died because of COVID-19 [7]. Headache, myalgia, hypogeusia, hyposmia, dizziness, and fatigue are the most common neurological manifestations [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%